Wnt pathway: A mechanism worth considering in endocrine disrupting chemical action - ALTURFAN, EBRU IŞIK (SAGE PUBLICATIONS INC, 2020)
Endocrine disrupting chemicals (EDCs) are defined as exogenous substances that can alter the development and functioning of the endocrine system. The Wnt signaling pathway is an evolutionarily conserved pathway consisting of proteins that transmit cell-to-cell receptors through cell surface receptors, regulating important aspects of cell migration, polarity, neural formation, and organogenesis, which determines the fate of the cell during embryonic development. Although the effects of EDCs have been studied in terms of many molecular mechanisms; because of its critical role in embryogenesis, the Wnt pathway is of special interest in EDC exposure. This review provides information about the effects of EDC exposure on the Wnt/beta-catenin pathway focusing on studies on bisphenol A, di-(2-ethylhexyl) phthalate, diethylstilbestrol, cadmium, and 2,3,7,8-tetrachlorodibenzo-p-dioxin.
Keywords: Endocrine disrupting chemical; Wnt signaling pathway; bisphenol A; phthalate; CATENIN SIGNALING PATHWAY; BISPHENOL-A EXPOSURE; RENAL-CELL CARCINOMA; BETA-CATENIN; MOUSE UTERUS; STEM-CELLS; RAT-BRAIN; EXPRESSION; RECEPTOR; TOXICITY